The Victorian supernatural (Cambridge University Press, 2004)
This collection brings together essays by scholars from literature, history of art and history of science which explore the diversity of Victorian fascination with the supernatural: ghosts and fairies, table-rappings and telepathic encounters, occult religions and the idea of reincarnation, visions of the other world and a reality beyond the everyday. These essays demonstrate that the supernatural was not simply a reaction to the "post-Darwinian loss of faith", but was embedded in virtually every aspect of Victorian culture.